Comparative genetic structure in two high-dispersal prawn species from the south-west Indian Ocean. Issue 4 (1st December 2017) - Mkare, TK; Groeneveld, JC; Teske, PR; Matthee, CA
Abstract : The penaeid prawns Fenneropenaeus indicus and Metapenaeus monoceros support shallow-water prawn fisheries in the south-west Indian Ocean. They are sympatric and have similar life histories, including developmental stages that depend on estuarine and marine habitats and a short dispersal duration. Nevertheless, M. monoceros juveniles display a more generalist habitat preference in estuaries and recruit to offshore habitats during a different season than F. indicus . We hypothesised that these differences would affect dispersal patterns, leading to dissimilar geographic genetic structure between the two taxa. Given their short dispersal phase, we also hypothesised that the Mozambique Channel would form a barrier to dispersal between the southeastern African mainland and Madagascar sites. Population differentiation was assessed based on analysis of mitochondrial DNA control-region sequences. Both species displayed high haplotype and low nucleotide diversity. Pairwise ϕST statistics supported the existence of admixed populations along the African mainland sites for both species, with geographic distance isolating populations at the extremes of the sampled range (Kenya and east coast of South Africa). The Madagascar population differed significantly from African mainland populations. The concordant patterns in population differentiation suggest that F. indicus and M. monoceros can be considered as single African stocks, or fisheries management units.